Low cost, facile, environmentally friendly all biomass-based squid ink-starch hydrogel for efficient solar-steam generation - Xu, Yuanlu; Xiao, Xin; Fan, Xinfei; Yang, Yi; Song, Chengwen; Fan, Yaofang; Liu, Yanming (Journal of materials chemistry. A, Materials for energy and sustainability, 2020)
The emerging solar-steam generation is recognized as one of the promising pathways to mitigate the global water crisis, but has a major obstacle: the development of sustainable solar-driven water evaporators with favorable evaporation performance. In this work, an all biomass-based hydrogel evaporator was fabricated for efficient solar steam generation, in which squid ink was employed as the photothermal material and starch as the hydrogel matrix. It was found that the hydrogel evaporator achieved a high water evaporation rate of approximately 2.07 kg m −2 h −1 under 1.0 sun with a corresponding energy efficiency of about 93.7%, arising from its excellent light absorption, light-to-heat conversion, energy confinement, wettability and water replenishment. Additionally, the evaporation performance can be further improved to evaporation rate of 2.62 kg m −2 h −1 and energy efficiency of 108.1% by capturing the environmental energy through simply increasing the evaporator height from 5 to 50 mm. For seawater desalination, the prepared evaporator exhibited both high salt resistance and good self-regeneration ability that ensure its promise for long-term practical application. The Na + concentration in the collected water was less than 1.0 mg L −1 . Thus, this work opens up a fascinating avenue for developing a novel hydrogel evaporator to providing potable and clean water. An all biomass-based hydrogel evaporator was fabricated for efficient solar steam generation, in which squid ink was employed as the photothermal material and starch as the hydrogel matrix.